Hubungan Antara Tingkat Kecemasan dan Kualitas Tidur dalam Menghadapi Ujian OSCE pada Mahasiswa - Chandra Dian Natalia; Betie Febriana; Wahyu Endang Setyowati (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
The Objective Structured Clinical Examination (OSCE) is a form of evaluation that demands the physical and mental readiness of nursing students. Academic pressure, the demands of clinical performance, and the fear of failure can trigger anxiety, potentially disrupting sleep patterns. Poor sleep patterns can impact nursing students' concentration, memory, and academic performance.  This study used a quantitative design with a cross-sectional approach. The population of this study were students of the Faculty of Nursing, Muhammadiyah University of Semarang who were taking the OSCE exam. The sample size was 119 respondents, taken using a proportionate random sampling technique. Data collection was carried out using the Hamilton Anxiety Rating Scale (HARS) questionnaire to measure anxiety levels and the Pittsburgh Sleep Quality Index (PSQI) to assess sleep patterns. Data analysis was carried out univariately and bivariately using the Spearman Rank statistical test. The results showed that most respondents were 20 years old (83.2%) and female (82.4%). Most students experienced mild anxiety (43.7%) and had good sleep quality (58.8%). The Spearman Rank test results showed a correlation value (r) = 0.898 with a p-value = 0.000 (p <0.05), which means there is a very strong and significant relationship between students' anxiety levels and sleep patterns in facing the OSCE exam.  There is a very strong and significant relationship between students' anxiety levels and sleep patterns during the OSCE.